Introduction to world religions and belief systems - Cornelio, Jayeel; Sapitula, Manuel Victor; Calano, Mark Joseph (Sampaloc, Manila : Rex Book Store, Inc., 2019)
"Introduction to World Religions and Belief Systems exposes students to the rich history, beliefs, and practices of various religions in the world today. By drawing insights from philosophy and the social sciences, students can reflect on contemporary religious issues affecting Philippine society. Using specific case studies and other activities, this book bravely confronts issues such as religious violence, the decline of religion, and the peace process. It also invites students to a world of deep thought with massive consequences on life, both optimistic and unsettling." -- Provided by publisher.
Includes bibliographical references.
English text.
Keywords: Religions; Religions -- history; Religions -- history -- problems, exercise, etc